1980
DOI: 10.1177/014662168000400302
|View full text |Cite
|
Sign up to set email alerts
|

Is a Behavioral Measure the Best Estimate of Behavioral Parameters? Perhaps Not

Abstract: In many areas of psychological research various measurement procedures are employed in order to obtain estimates of some set of parameter values. A common practice is to validate one measurement device by demonstrating its relationship to some criterion. However, in many cases the measurement of that criterion is less than a perfect estimate of true parameters. Self-report measures are often validated by comparing them with behavioral measures of the dimension of interest. This procedure is only justifiable in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 23 publications
2
42
0
Order By: Relevance
“…However, as a number of authors have pointed out, self-report measures are indispensable in organizational research (Gupta and Beehr 1982;Podsakoff and Organ 1986). Indeed, in certain research contexts, self-reports may provide more accurate estimates of population parameters than behavioral measures (Howard et al, 1980). Finally, as previously mentioned, the instrument used in this study has been found to be highly reliable and psychometrically sound.…”
Section: Discussionmentioning
confidence: 63%
“…However, as a number of authors have pointed out, self-report measures are indispensable in organizational research (Gupta and Beehr 1982;Podsakoff and Organ 1986). Indeed, in certain research contexts, self-reports may provide more accurate estimates of population parameters than behavioral measures (Howard et al, 1980). Finally, as previously mentioned, the instrument used in this study has been found to be highly reliable and psychometrically sound.…”
Section: Discussionmentioning
confidence: 63%
“…Lee and Cornell convincingly argued that their study was the first published study to partially test the validity of the Olweus measure (and the reader is referred to their literature for a more thorough review of this claim). Finally, in what the researchers believe to be one of the few studies of its kind, Howard et al (1980) conducted a series of three studies comparing self-report measures of behavior to three other types of behavioral measures (i.e., self-report, other-report, role play, and actual observation). They studied three different behaviors, and concluded in all cases self-report measures of behavior are always as good and in some cases better than other behavioral measures.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…However, as a number of authors have pointed out, self-report measures are indispensable in organizational research (Podsakoff and Organ, 1986). Indeed, in certain research contexts, selfreports may provide more accurate estimates of population parameters than behavioral measures (Howard et al, 1980). Finally, a comparison of business students and practitioners would be another productive avenue.…”
mentioning
confidence: 99%